The effect of nano-twins on the thermoelectric properties of Ga2O3(ZnO)m (m = 9, 11, 13 and 15) homologous compounds. Issue 15 (December 2020) - Alvarez-Ruiz, D.T.; Azough, F.; Slater, Thomas; Day, Sarah J.; Freer, R.
Abstract: Ga2 O3 (ZnO)m ( m = integer) homologous compounds are naturally occurring nanostructured materials. Their intrinsically low thermal conductivity makes them attractive for thermoelectric applications. High density Ga2 O3 (ZnO)m ( m = 9, 11, 13, and 15) single phase ceramics were prepared by solid-state reaction. Nano-sized, twin-like V-shaped boundaries parallel to b -axis (apex angle ∼ 60°) were observed for all compositions. Atomic resolution Z -contrast imaging and EDS analysis for m = 15 showed segregation of Ga ions at the interface of V-shaped twin boundaries. Thermal and charge transport properties depend on the value of m . Compositions with m = 9 exhibited very low lattice thermal conductivity of 2 to 1.5 W/m.K at 300 K–900 K; compositions with m= 15 showed improved power factor of 140 μW/m. K 2 at 900 K leading to a thermoelectric figure of merit ( ZT value) of 0.055. This study explores the structural variants and routes to improve the thermoelectric properties of these materials